Filosofía del desastre: El terremoto de Japón de 2011 y el viaje-producto - Korstanje, Maximiliano E. (Nómadas. Critical Journal of Social and Juridical Science, 2012)
A wide set of mechanism to understand what is happening surfaces in contexts of emergencies in order for social bondage not to be disintegrated. Nationalism and cultural heritage are new elements of a neo-consumerism. These work as a form of understanding the environment and the connection of self with nature. Basically, the tragedy suggests a radical determination but the personal strength can overcome its obstacles. Following this, the pride for the own culture seems to be over-exaggerated after a episode of this magnitude. In this vein, we examine not only the coverage of journalists and newspapers in the Japan´s quakes but also refer to the elements that intervene in the configuration of nuclear threat which was surely embodied into the figure of Fukuyima´s reactor.